2016
DOI: 10.1177/1550059416652055
|View full text |Cite
|
Sign up to set email alerts
|

Slow Activity in Focal Epilepsy During Sleep and Wakefulness

Abstract: Patients with focal epilepsy showed a pattern of power increases characterized by a selective slow wave activity enhancement over the epileptic regions during daytime and sleep. This phenomenon was stronger and asymmetric during the first sleep cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 53 publications
5
36
1
Order By: Relevance
“…Advanced EEG analyses demonstrate that delta activity of the UH results from an interhemispheric communication breakdown of electrical signals between the two hemispheres and that this might, in turn, interfere with the UH contribution to recovery, i.e., plasticity processes (Graziadio et al, 2012; Assenza et al, 2013b). Patients with focal epilepsy show an increase in delta activity during daytime and sleepiness, but its biological meaning is uncertain (Pellegrino et al, 2017). …”
Section: Spontaneous and Task-related Oscillatory Activitymentioning
confidence: 99%
“…Advanced EEG analyses demonstrate that delta activity of the UH results from an interhemispheric communication breakdown of electrical signals between the two hemispheres and that this might, in turn, interfere with the UH contribution to recovery, i.e., plasticity processes (Graziadio et al, 2012; Assenza et al, 2013b). Patients with focal epilepsy show an increase in delta activity during daytime and sleepiness, but its biological meaning is uncertain (Pellegrino et al, 2017). …”
Section: Spontaneous and Task-related Oscillatory Activitymentioning
confidence: 99%
“…Second, our source analysis revealed that, although theta is a signature generated over a large network covering multiple fronto-central-parietal regions, the activity mostly relevant to motor performance was generated in L dPMC. Previous studies demonstrated that theta can be generated locally, within the sensori-motor regions during the late stages of motor learning (Perfetti et al, 2011b ), in the fronto-parietal cortex for motor planning and on-line motor adjustments (Perfetti et al, 2011a ) and as signature of brain plasticity in both physiological and pathological conditions (Kirov et al, 2009 ; Hung et al, 2013 ; Assenza et al, 2015 ; Pellegrino et al, 2016c ; Tombini et al, 2012 ). As our task was explicitly designed to engage L dPMC, which is well known for its role in motor control, we could infer that this specific region generates theta waves to perform both motor re-evaluation and motor reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity induction has been usually measured as changes of brain excitability [ 10 , 38 ]. However, previous studies have demonstrated that both noninvasive brain stimulation and cortical plasticity are also associated with changes of brain rhythms and synchronization [ 39 41 ]. Conversely, robust and consistent evidence suggests that also neurological conditions translate into changes of brain activity and synchronization [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have demonstrated that both noninvasive brain stimulation and cortical plasticity are also associated with changes of brain rhythms and synchronization [ 39 41 ]. Conversely, robust and consistent evidence suggests that also neurological conditions translate into changes of brain activity and synchronization [ 41 ]. For instance, an impairment of cortical synchronization is often found at the first stages of neuropsychiatric conditions, up to the healthy subjects who own an increased risk [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%